Neutral imino-methyl benzenesulfonate-ligated Pd(II) complexes and implications in ethylene polymerization - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Mote, Nilesh R.; Manod, M.; Gonnade, Rajesh G.; Chikkali, Samir H. (ACS Omega, 2019)
A reaction between sodium 2-formylbenzenesulfonate and aniline revealed the near-quantitative (91%) formation of sodium-2-((phenylimino)methyl)benzenesulfonate L1. The identity of L1 was unambiguously ascertained using spectroscopic and analytical methods. The scope of this methodology was widened and various electron-donating amines were treated with sodium 2-formylbenzenesulfonate, and a small library of 6 imine ligands L2-L6 was generated. When L2 was treated with [(COD)PdMeCI], instead of the anticipated [L2PdMe(DMSO)] complex, the formation of [(DMSO)(2)Pd2Cl2Me2] Pd Dim was observed. Nevertheless, the desired imino-methyl benzenesulfonate-ligated palladium complex [L2PdMe(Lu)] C1 was obtained by in situ abstraction of chloride and addition of bulky 2,6-lutidine as the donor group. The observation of characteristic Pd-Me protons at 0.06 ppm and the corresponding carbon at -8.1 ppm indicated the formation of C1. These 1D NMR observations were corroborated by 2D C-H correlation spectra and mass analysis, and the existence of C1 was unambiguously ascertained. Along the same lines, L4 and L5 were treated with a palladium precursor to produce [L4/SPdMe(Lu)]-type complexes C2-C3 in 55-84% yield, and their identity was established by using a combination of spectroscopic tools, analytical methods, and single-crystal X-ray diffraction. The synthetic utility of C1-C3 has been demonstrated by utilizing these complexes in the insertion polymerization of ethylene to polyethylene.